Can Basic Characteristics Estimate Body Composition in Early Infancy?. Issue 3 (March 2018) - Liotto, Nadia; Roggero, Paola; Bracco, Beatrice; Menis, Camilla; Morniroli, Daniela; Perrone, Michela; Giannì, Maria L.; Mosca, Fabio
ABSTRACT: Objectives: Increasing evidence demonstrates that body composition in early life contributes to the programming of health later in life in both full-term and preterm infants. Given the important role of body composition, the increased availability of easy, noninvasive, and accurate techniques for its assessment has been recommended. The aim of the present study was to identify basic characteristics and anthropometric measurements that best correlate with body composition in infants. Methods: Anthropometric measurements and body composition assessed by air-displacement plethysmography were assessed either at birth or at term-corrected age in 1239 infants (654 full-term, 585 preterm). The associations of sex, GA (gestational age), and weight with FFM (fat-free mass) and FM (fat mass) adjusted by length (g/cm) were investigated by multiple linear regression models. Bland-Altman tests were performed, and an equation for calculating FFM was determined. Results: Preterm infants exhibited increased FM and reduced FFM compared with full-term infants (477.6 ± 204 vs 259.7 ± 147 g and 2583 ± 494 vs 2770 ± 364 g, respectively). GA, male sex, and weight were positively associated with FFM ( r 2  = 0.806, P  < 0.0001; 6.1 g of average bias). GA and male sex were negatively associated with FM, whereas weight was positively associated with FM ( r 2  = 0.641, P  < 0.0001; 4.9 g of average bias). Conclusions: The assessment of body composition represents the criterion standard. When body composition assessment is not feasible, the equation based on sex, GA, and anthropometric measurements can be useful in predicting body composition in both full-term and preterm infants.